(untitled) (Journal of Medical & Health Sciences Review, 2025)
Traditional herbal medicines play a significant role in management and treatment of diseases and are gaining attention across the glob to control the diseases. Calotropis gigantea is a medicinal plant and have been using since ancient times for the treatment of bacterial infections, abdominal and skin diseases, wounds infections, insect bites and even for inhibiting certain cancer cells growth. Cyclotides are cyclic cyctine-rich miniproteins having three inter-locking disulphide bridges between six conserved cysteine amino acids. These cyclopeptides have exceptional properties like resistance to thermal, chemical and enzymatic degradation which is mainly due to their three-dimensional folding of polypeptide chain. The plant based bioactive cyclopeptides are novel for drug development. The current study describes the isolation and characterization of cyclotides from leaves of C. gigentea involving its extraction, isolation and purification by applying different techniques. Purified cyclopeptides were used as antibacterial agents against two gram positive bacteria i.e Staphylococcus aureus and Bacillus subtilis and two gram negative bacteria i.e Escherichia coli, Pseudomonas aeruginosa. Results showed the inhibited growth of these microbes due to antibacterial activities of cyclotides.